INSIGHTS OF TWO CHURCH DENOMINATIONAL FIGURES ON THE AESTHETICS OF TRIUNE IN HANS URS VON BALTHASAR - Enjeli Putri Amisani; Nazareth Dealova, Nani Sunarsi, Yosep Anthonius, Vernike Niatda Zebua, Aprianto Wirawan, Reynhard Ma (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Background of this research is to find out and explain the views of several church denomination figures about the aesthetics of the Trinity related to theology according to Hans Urs Von Balthar. One religion is Protestant Christianity but different church denominations and of course also different worship procedures. In this paper, the differences between the church denominations will not be explored. The main thing is that all church denominations believe in the Triune God. Instead, let's look for sources from the leaders of each church denomination, to find out how they view the aesthetics of the Trinity related to theology and which will unite the existing differences. The sources taken are from several journals consisting of English and Indonesian journals. In addition, researchers conducted direct interviews and written interviews with several church denomination leaders from the Kalimantan Evanglis Church (GKE) and the Seventh-day Adventist Church or better known as the Adventist Church.